Rethinking Tadabbur (Contemplation) al-Qur’ān through the Lens of Tajdīd (Renewal) Approach - Shehu, Fatmir; Boudjemline, Bilal (IIUM Journal of Religion and Civilisational Studies, 2026)
This study seeks to examine the rethinking of tadabbur (contemplation) through the lens of the tajdīd (renewal) approach emphasising its appropriate implementation while dealing with Allah (ﷻ)’s Speech, al-Qur’ān, revealed to the Prophet (ﷺ) as a divine miracle for all times. Al-Qur’ān was not revealed for the mere recitation and memorisation; rather, its purpose was tadabbur of its text in a deep sense, including the application of the extracted rulings to various aspects of life. Its aim is to revisit the concept of tadabbur al-Qur’ān as practiced by the Prophet (ﷺ), his Ṣaḥābah, and Tābi‘īn, and how it later shifted toward a focus on recitation and memorisation, often at the expense of deeper reflection. Descriptive and analytical methods are used in the entire paper. This paper discusses tadabbur al-Qur’ān and other related terms, sharia ruling on it, and mufassirūn’s consensus on its necessity, importance, and purposes, including its effect on Ṣaḥābah and its practical impact on one’s īmān (conviction) and personality. The findings show that through the tajdīd (renewal) approach, tadabbur al-Qur’ān is apprehended as more than just a mere recitation or textual reading. It becomes a transformative instrument in which al-Qur’ān engages people’s hearts and intellects, enabling them to shape their attitudes, develop their personalities, mature their decisions, and understand their life direction.